Do Rates of Mental Disorders and Existential Distress among Advanced Stage Cancer Patients Increase as Death Approaches? - Lichtenthal, Wendy G. (2009)
OBJECTIVE: To determine if the prevalence of mental disorders and related factors increase as advanced cancer patients get closer to death. METHOD: Baseline, cross-sectional data from 289 patients who were assessed prior to their death as part of a multi-site, longitudinal, prospective cohort study of advanced cancer patients. Major Depressive Disorder, Generalized Anxiety Disorder, Panic Disorder, and Posttraumatic Stress Disorder were assessed using the Structured Clinical Interview for the DSM-IV Axis I Disorders (SCID-I). Other factors examined included existential well-being, patient grief about their illness, physical symptom burden, terminal illness acknowledgment, peacefulness, and the wish to live or die. RESULTS: Closeness to death was not associated with higher rates of mental disorders. Patients closer to death exhibited increased existential distress and physical symptom burden, were more likely to acknowledge being terminally ill, and were more likely to report an increased wish to die. CONCLUSION: Results do not provide support for the common clinical assumption that the prevalence of depressive and anxiety disorders increases as death nears. However, patients' level of physical distress, acknowledgment of terminal illness, and wish to die, possibly reflecting acceptance of dying, increased as death approached. Longitudinal studies are needed to confirm individual changes in rates of mental disorder as patients approach death.